The Effectiveness of the Implementation of Termination of Prosecution in Criminal Cases of Assault Based on Restorative Justice (Case Study of the Kapuas Hulu District Attorney's Office) - Rustam Efendi P Simarmata; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This research is motivated by the increasing use of restorative justice mechanisms in resolving criminal acts of assault as a form of reforming the criminal justice system oriented towards more humanistic, participatory justice and social restoration. The Kapuas Hulu District Attorney's Office is one of the law enforcement institutions that implements the termination of prosecution based on restorative justice in accordance with the Republic of Indonesia Attorney General's Regulation Number 15 of 2020. This study aims to determine the implementation of the termination of prosecution in assault cases based on restorative justice, analyze weaknesses in its implementation, and assess its current effectiveness and potential effectiveness in the future. The research method used is normative juridical with a socio-legal approach (socio-legal research/studies) needed to address issues of social injustice. Data sources consist of primary, secondary, and tertiary legal materials which are analyzed qualitatively to produce a comprehensive picture of the implementation of the policy of termination of prosecution based on restorative justice. The results of the study indicate that the implementation of restorative justice in the Kapuas Hulu District Attorney's Office has quite high effectiveness, evidenced by the acceleration of case resolution, recovery of victim losses, and the creation of harmonious social relations after the case. However, various weaknesses remain, such as limited mediator capacity, a lack of public understanding of restorative justice, potential social pressure on victims to reconcile, and suboptimal oversight of the implementation of peace agreements. This research emphasizes the need to improve the quality of human resources, strengthen regulations, and optimize institutional support to ensure the implementation of restorative justice is more effective in the future.